A Study of the Needs and Guidelines for Reducing Learning Regression in Small Schools under the Office of Kamphaeng Phet Primary Educational Service Area 1 - Menkhong, Jittra; Nakai, Nikom (Academic MCU Buriram Journal, 2025)
The purposes of this research were: 1) to study the necessity to reduce learning regression in small schools, and 2) Study the approach to reduce learning regression of small school administrators. The population consisted of school administrators and academic teachers from 125 schools, consisting of 78 school administrators and 97 teachers. The instrument used was a questionnaire. The statistics used for data analysis were percentage, mean, standard deviation, and index of the importance of necessity. The data was analyzed by content analysis. The research results were found that: 1. The study of the needs to reduce the learning regression of small schools was found that the index of the priority of the needs to reduce the learning regression of small schools found that overall was equal to .23. When considering each aspect, it was found that the design of the learning management process and new teaching model had the highest priority index value, equal to .25. 2. The guidelines for reducing the learning regression of small school administrators were found that the experts had the highest consensus as follows: (1) In terms of creating participation in learning management, school administrators and teachers collaborated with parents and the community to create an environment that facilitates, supports and promotes student learning. (2) In terms of developing digital media repositories and using technology systematically, school administrators and teachers can design the creation of learning media without limitations of time and place. (3) In terms of promoting and developing teacher learning management, administrators must be leaders of development. (4) In terms of designing the learning management process and new teaching model, school administrators and teachers have a variety of teaching models that promote the creation of knowledge for students.